Patterns and correlates of smoking among randomly selected former athletes - Wojtas-Ślubowska, Donata; Hurnik, Elżbieta (Polish Journal of Public Health, 2009)
Introduction. The relationship between smoking and inactivity or moderate physical activity is well documented, but little is known about the relationship between smoking and participation in competitive sports.Aim. The objectives of our investigation were to present prevalence data for cigarettes smoking among athletes, describe the direction of changes in smoking habits after finishing their sports career, and examine the independent risk factors of smoking among female and male former athletes.Material and methods. Randomly selected Polish former athletes (n=351, aged 18-66 yr) responded to an anonymous questionnaire regarding smoking during their sports career, period and level of participation in competitive sports in the past, and current smoking status, level of leisure time for physical activity, and socioeconomic status. Wilcoxon`s signed rank test was used to determine changes in smoking behaviours during and after finishing respondents` sports career. Risk factors of smoking were identified through the logistic regression analysis.Results. The prevalence and intensity of smoking among men and women during their sports career were low. The increase in prevalence of smoking after finishing sports career was observed among both men (p